Variations in Static Force Control and Motor Unit Behavior with Error Amplification Feedback in the Elderly - Chen, Yi-Ching; Lin, Linda L.; Lin, Yen-Ting; Hu, Chia-Ling; Hwang, Ing-Shiou (Frontiers in Human Neuroscience, 2017)
Error amplification feedback is a promising approach to advance visuomotor skill. As error detection and visuomotor processing at short time scales decline with age, this study examined whether older adults could benefit from error amplification feedback that included higher-frequency information to guide a force-tracking task. Fourteen young and fourteen older adults performed low-level static isometric force-tracking with visual guidance of typical visual feedback and error amplification feedback containing augmented high-frequency errors. Stabilogram diffusion analysis was used to characterize force fluctuation dynamics. Also, the discharge behaviors of motor units and pooled motor unit coherence were assessed following the decomposition of multi-channel surface electromyography. Error amplification produced different behavioral and neurophysiological impacts on young and older adults. Older adults exhibited inferior task accuracy with error amplification feedback than with typical visual feedback, but not young adults. Although stabilogram diffusion analysis revealed that error amplification led to a significant decrease in critical time points for both groups, error amplification potentiated the critical point of force fluctuations, short-term effective diffusion coefficients, and short-term exponent scaling only for the older adults. Moreover, in older adults, error amplification added to the size of discharge variability of motor units and discharge regularity of cumulative discharge rate, but suppressed the pooled motor unit coherence in the 13-35 Hz band. Virtual error amplification alters the strategic balance between open-loop and closed-loop controls for force-tracking. Contrary to expectations, the prevailing use of closed-loop control with error amplification that contained high-frequency error information enhanced the motor unit discharge variability and undermined the force steadiness in the older group, concerning declines in physiological complexity in the neurobehavioral system and the common drive to the motoneuronal pool against force destabilization.